Peran Orang Tua dalam Mencegah Kenakalan Remaja di Huta I Bandar Malela - Tanjung, Muaz; Rubino; Ardianti, Hafizda; Putri Irawan, Ravika; Rama Noprialdi Ginting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The role of parents is a form of obligation and duty that should be carried out by every parent, and where taking each of these roles has an influence on the level of independence of adolescent children for the next life. And the role of parents is not only seen as the foundation of teachers, but can also act as mentors and models for each of their children. In the process carried out by each parent, various problems often arise. Be it in terms of the child's social environment, parents' mistakes in pampering their children, and there are even some parents who have succeeded in forming children's independence so that they become good teenagers in the future. However, it is known that teenagers who commit crimes or delinquencies are generally due to a lack of self-control and actually abuse their way of controlling themselves, and even like to make their own rules without paying attention to the existence of other people around them. And in the Huta I area of Bandar Malela, researchers see and do very rarely, even a small incidence of juvenile delinquency in this village, because parents are smart in educating and supervising every child from childhood to adolescence. And this research aims to describe the role of parents in Huta I Bandar Malela in preventing juvenile delinquency. This research is also descriptive research using a qualitative approach. The subjects of this research were 6 parents who had teenage children aged 14 to 21 years, who lived in Huta I Bandar Malela, Gunung Maligas District, Simalungun Regency. The object of this research includes the role of parents in preventing juvenile delinquency. Data collection was carried out using observation, interview and documentation techniques. The results of this research show that parents in Huta I Bandar Malela have been able to carry out their roles as educators, encouragers, supervisors, communicators and friends of their children so as to avoid juvenile delinquency